2020
DOI: 10.1186/s12883-020-02007-5
|View full text |Cite
|
Sign up to set email alerts
|

A distinct neuromelanin magnetic resonance imaging pattern in parkinsonian multiple system atrophy

Abstract: Background Parkinsonian variant of multiple system atrophy is a neurodegenerative disorder frequently misdiagnosed as Parkinson’s disease. No early imaging biomarkers currently differentiate these disorders. Methods Simple visual imaging analysis of the substantia nigra and locus coeruleus in neuromelanin-sensitive magnetic resonance imaging and nigrosome 1 in susceptibility-weighted sequences was performed in thirty patients with parkinsonian variant of multiple system atrophy fulfilling possible/probable se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…Diagnostic accuracy may be improved by using neuromelanin-sensitive acquisitions based on explicit magnetization transfer effects [22,23] or incorporating other metrics, such as UPDRS score or MRI metrics from other structures, in machine learning classification algorithms. Metrics derived from neuromelanin-sensitive data show promise for differential diagnosis of parkinsonian syndromes [51][52][53] and further development of these metrics may allow for accurate discrimination of SWEDD from PD.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy may be improved by using neuromelanin-sensitive acquisitions based on explicit magnetization transfer effects [22,23] or incorporating other metrics, such as UPDRS score or MRI metrics from other structures, in machine learning classification algorithms. Metrics derived from neuromelanin-sensitive data show promise for differential diagnosis of parkinsonian syndromes [51][52][53] and further development of these metrics may allow for accurate discrimination of SWEDD from PD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MSA-P show normal neuromelanin in the substatia nigra and the locus coeruleus, similar to normal brains and allowing the distinction compared to idiopathic Parkinson ones [11]. The pontine hot-cross bun is of lower visual grade in MSA-P than in MSA-C on T2 * weighted imaging [12].…”
Section: Multiple System Atrophy With Predominant Parkinsonian Featuresmentioning
confidence: 97%
“…Recently, it has been reported that the combined visual analysis of SN (by using NM-MRI and nigrosome-1 imaging, displaying normal NM in SNc and nigrosome-1 loss) has enabled the distinction of MSA-P from PD and healthy controls [56]. Moreover, it has also Moreover, the imaging of nigrosome-1 with 3T MR has been demonstrated to differentiate drug-induced Parkinsonism from idiopathic PD with elevated accuracy, thereby being of assistance in screening patients who required dopamine transporter imaging [49].…”
Section: Nigrosome-1 Imagingmentioning
confidence: 99%
“…Recently, it has been reported that the combined visual analysis of SN (by using NM-MRI and nigrosome-1 imaging, displaying normal NM in SNc and nigrosome-1 loss) has enabled the distinction of MSA-P from PD and healthy controls [56]. Moreover, it has also been described that a stratification of the swallow tail sign, using a scale on SWI-map imaging, may serve as a useful imaging biomarker regarding the differential diagnosis of Parkinsonism [57].…”
Section: Nigrosome-1 Imagingmentioning
confidence: 99%